2000
DOI: 10.1207/s15327590ijhc1202_3
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Navigation Aids for Two World Wide Web Systems

Abstract: In spite of the radical enhancement of Web technologies, many users still continue to experience severe difficulties in navigating Web systems. One way to reduce the navigation difficulties is to provide context information that explains the current situation of Web users. In this study, we empirically examined the effects of 2 types of context information, structural and temporal context. In the experiment, we evaluated the effectiveness of the contextual navigation aids in 2 different types of Web systems, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…Researchers have studied a variety of topics on how children and adults learn to use computers from the cognitive developmental perspective. Five of the topics are of major importance: (1) developmental appropriateness in children's learning computers (Houston, 1985;Silvern, Williamson, and Countermine, 1988), (2) children's skills of programming or using computer programs such as word processing (Sebrechts, Deck, Wagner, and Black, 1984;Sprigle and Schaefer, 1984), (3) beliefs, conceptions, and representations of computers (Kay and Black, 1990;Krendl and Broihier, 1992;Mioduser, Venezky, and Gong, 1996;Scaife and van Duuren, 1995;van Duuren and Scaife, 1995), (4) perception, memory, and metacognition in learning computers (Calvert, 1994;Clements and Nastasi, 1999), and (5) cyberspace navigation skills (Chiu and Wang, 2000;Head, Archer, and Yuan, 2000;McDonald and Stevenson, 1998;Park and Kim, 2000;Westerman, 1995;Xu, Dainoff, and Mark, 1999;Zizi and Beaudouin-Lafon, 1995).…”
Section: Human Development and Learning To Use Computersmentioning
confidence: 99%
“…Researchers have studied a variety of topics on how children and adults learn to use computers from the cognitive developmental perspective. Five of the topics are of major importance: (1) developmental appropriateness in children's learning computers (Houston, 1985;Silvern, Williamson, and Countermine, 1988), (2) children's skills of programming or using computer programs such as word processing (Sebrechts, Deck, Wagner, and Black, 1984;Sprigle and Schaefer, 1984), (3) beliefs, conceptions, and representations of computers (Kay and Black, 1990;Krendl and Broihier, 1992;Mioduser, Venezky, and Gong, 1996;Scaife and van Duuren, 1995;van Duuren and Scaife, 1995), (4) perception, memory, and metacognition in learning computers (Calvert, 1994;Clements and Nastasi, 1999), and (5) cyberspace navigation skills (Chiu and Wang, 2000;Head, Archer, and Yuan, 2000;McDonald and Stevenson, 1998;Park and Kim, 2000;Westerman, 1995;Xu, Dainoff, and Mark, 1999;Zizi and Beaudouin-Lafon, 1995).…”
Section: Human Development and Learning To Use Computersmentioning
confidence: 99%
“…It has been proposed that a high structural design Web-site allowed users to understand the contents of the page more precisely and to search for detailed information more easily (Park & Kim, 2000;Miles, Howes, & Davies, 2000). In their two experiments, Park and Kim (2000) evaluated the effectiveness of contextual navigation aids in two different types of Web systems, an electronic commerce system that has a well-defined structure and a content dissemination system that has an ill-defined structure.…”
Section: Discussionmentioning
confidence: 99%
“…In their two experiments, Park and Kim (2000) evaluated the effectiveness of contextual navigation aids in two different types of Web systems, an electronic commerce system that has a well-defined structure and a content dissemination system that has an ill-defined structure. The results of their experiments showed that context information obtained from a welldefined structure improved the users' navigation patterns, increased their subjective convenience of navigation and developed their degree of comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…This problem is known as disorientation [18]. Because of such a condition, MacKenzie and Cockburn [19] argue that the length of the navigation period impacts the revisitation, and the visited information space [17]. Thus, it is argued that when users navigate a Website and becomes disoriented, they may have lost what they already collected.…”
Section: Cost Of Information Searchmentioning
confidence: 99%